Efektivitas Komunikasi Pemangku Adat Dalam Pencegahan Konflik Keagamaan Di Kecamatan Siporok Kabupaten Tapanuli Selatan - Latip Kahpi; Asriana Harahap (IAIN Padangsidimpuan, 2020)
AbstractThis study is a qualitative research,the method of the study is descriptive interpretative methods, which describe and interpret what their research results. The Source of the data are primary and secondary sources of data. The primary source of dataisTraditional Leadersin the district of Sipirok, SouthTapanuli, which consists of MangarajaTenggar, Sire Marduri, Mangaraja Hurning, Mangaraja Lintong, Sutan Soripada Parlindungan, Hamdan Siregar. Secondary sources of data is chairman of KUA (Office of Religious Affairs in the district of Sipirok), Akhirul Pane (MUI in the districts of Sipirok) Rev. A. Sinaga, and Rev. Maruli Hutagalung. The objective of research is to find out how the forms of communication of traditional leaders in the prevention of religious conflicts in the district Sipirok, to know the effectiveness of forms of traditional leaders’communication. To know the obstacles and the implications of traditional leaders’ communication in the prevention of religious conflict in the district of Sipirok, South Tapanuli. The result of the research which there are three forms of traditional leaders’ communication in the prevention of religious conflicts, they are interpersonal communication, group communication, and communication that using mass media. The obstacles of traditional leaders’ communication namely, internal and external obstacles. The internal obstacle is exclusive, traditional leaders is very closed off to the public, and also there is no room for the public to provide space and opportunity to express their opinions openly and freely. External obstacles include the occurrence of language differences especially with immigrant communities that cause misunderstanding between traditional leadership and the community.Keywords: Effectiveness, Indigenous Holders, and Religious Conflict.